Late Cenozoic Foreland‐to‐Hinterland Low‐Temperature Exhumation History of the Kashmir Himalaya. Issue 9 (17th September 2018) - Gavillot, Yann; Meigs, Andrew J.; Sousa, Francis J.; Stockli, Daniel; Yule, Doug; Malik, Manzoor
Abstract: New apatite and zircon (U‐Th)/He cooling ages quantify late Cenozoic exhumation patterns associated with fault activity across the Kashmir Himalaya. Apatite (U‐Th)/He (AHe) cooling ages of detrital grains from the Sub‐Himalayan foreland sediments indicate significant resetting. AHe data and thermal modeling reveal cooling and exhumation initiated by 4 Ma at the deformation front and by 2–4 Ma throughout other Sub‐Himalayan structures. Exhumation rates for Sub‐Himalayan structures are ≥1 mm/year. In the hinterland, thrust sheet samples from the Main Boundary thrust and Main Central thrust yield AHe cooling ages between 5.1 and 21.1 Ma. Published apatite fission track cooling ages (<3 Ma) and high exhumation rates (3.6–3.2 mm/year) across the Kishtwar window further to the north are consistent with AHe data from the Sub‐Himalayan structures. The pattern of cooling ages and rates indicates that exhumation occurs in association with changes in the Himalayan basal décollement ramp geometry. Hinterland zircon (U‐Th)/He (ZHe) data show a pronounced abundance and probability spike in cooling ages between 14 and 21 Ma, a period when Main Central thrust motion is well documented throughout the Himalaya. ZHe single‐grain ages from Sub‐Himalayan samples contain a nearly identical cluster from 16 to 23 Ma. Cooling patterns across the Kashmir Himalayas do not correlate spatially with modern monsoon precipitation, suggesting that climate‐related precipitation and exhumation are decoupled. Coeval translation over the basal décollement and distributed imbricate thrust deformation of the foreland in the upper plate characterizes fault‐related exhumation of the Sub‐Himalayan orogenic belt after 4 Ma. Plain Language Summary: Our new data document the timing of cooling of rocks brought to the surface during mountain building of the Kashmir Himalaya. Mineral grains eroded from the Himalaya and deposited in the plain are now exposed in the Sub‐Himalayan belt. The ages of these rocks that we have measured constrain the timing of burial and subsequent return to the Earth's surface (exhumation) during thrust fault‐related deformation. Analysis of apatite grains reveals that cooling and exhumation initiated by 4 Ma on the southernmost structure of the Kashmir Himalaya and by 2–4 Ma on other distributed faults in the Sub‐Himalayan belt. In the core of the mountain range rocks have young cooling ages (<3 Ma) related to high uplift rates within the Kishtwar window, a zone of localized deformation in the High Himalaya. Thus, outward growth of the Sub‐Himalayan belt occurred in concert with uplift in the hinterland over the past 4 Myr. Precipitation rates vary systematically from south to north across the Himalaya, but these variations are not synchronous with the pattern of cooling and exhumation in Kashmir Himalaya. This result suggests that climate does not drive crustal deformation. Instead exhumation patterns primarily reflect the location, geometry, and partitioning of faulting within the Himalaya. Key Points: In the Kashmir Himalaya thrust‐related cooling and exhumation initiated by 4 Ma at the deformation front and by 2–4 Ma throughout the Sub‐Himalayan structures A ramp geometry to the Himalayan basal décollement explains across‐ and along‐strike variation in uplift rates and exhumation history Distributed deformation between duplex growth in the hinterland and imbricate thrusts in the foreland since 4 Ma suggests a subcritical wedge state